(untitled) (Revista Contexto & Saúde, 2022)
The aim of the study was to analyze the effects of physical exercise on physical fitness and quality of life of patients with chronic renal failure undergoing hemodialysis. This is an intervention study, with a sample of 13 patients on hemodialysis at the Renal Clinic of Hospital São Vicente de Paulo. The program was applied in 2019/2 (August to December) and took place during the first two hours of hemodialysis (intradialitic), three times a week lasting 20/70 minutes. The same consisted of active stretching, warm-up, cycle ergometer training, resistance training and stretching. Participants in the physical exercise program showed improvement in all physical valences evaluated, occurring significantly in upper limb resistance (pre-test = 17.85 ± 4.54; post-test = 20.69 ± 7.62; p = 0.034) and handgrip strength (pre-test = 28.15 ± 9.39; post-test = 28.62 ± 12.61; p = 0.048), as well as a significant improvement in quality of life in pain domain (pre-test = 73.15 ± 26.92; post-test = 91.46 ± 18.78; p = 0.016), vitality (pre-test = 78.00 ± 15.48; post-test = 90.08 ± 9.03; p = 0.010) and social aspects (pre-test = 71.31 ± 28.63; post-test = 85.92 ± 22.42; p = 0.050). We conclude that the resistance exercise program has several benefits for patients on Hemodialysis.